Factors Influencing the Success of the Tefa Automotive Program in Improving the Work Skills of Private Vocational School Students Nias Regional Government - Sabar Jaya Zalukhu; Ambiyar; M. Giatman; Dedy Irfan (Postgraduate, University of Mataram, 2025)
The misalignment between Vocational High School (SMK) activities and the dynamics of industrial needs is a significant challenge in the vocational education system. This phenomenon not only has an impact on the increasing unemployment rate of vocational high school graduates but also has the potential to hamper innovation and competitiveness of the national industry due to the shortage of skilled workers who match market needs. One crucial problem that often arises in the context of vocational education in Indonesia is the disparity between the competencies produced by Vocational High School graduates and the specific demands required by the industrial world. This study aims to analyze the influence of internal and external factors on the success of the Teaching Factory (TEFA) program in improving student work skills at the Nias Regional Government Private Vocational High School. This study uses a quantitative approach with a correlation method. Data were collected through questionnaires given to students of the Light Vehicle Engineering Expertise Program who have participated in the TEFA program. Data analysis techniques used validity, reliability, and multiple regression tests. The results of the study indicate that internal factors, such as teacher competence, curriculum, facilities, and student involvement, as well as external factors such as industry partnerships, internship programs, and government support, significantly influence the success of TEFA. These findings underscore the importance of synergy between schools, industry, and government in providing vocational education that is responsive to the needs of the workforce.